KESEDIAAN MEMBAYAR WISATAWAN TERHADAP UPAYA PELESTARIAN MANGROVE DI PULAU PAHAWANG, KABUPATEN PESAWARAN, LAMPUNG - Boy Apriliawan; Indra Gumay Yudha; Suparmono Suparmono; Abdullah Aman Damai (Jurusan Akuakultur, Universitas Bangka Belitung, 2020)
Ecotourism on Pahawang Island is a well-known tourist destination in Pesawaran Regency, Lampung Province with has mangrove ecosystem covers an area of ​​141.94 ha. Unfortunately, in 2016, there was logging of the mangrove ecosystem on Pahawang Island which caused the mangrove ecosystem to suffer damage. This must be immediately responded to by conducting efforts to protect, conserve and manage the mangrove ecosystem by inviting the community to contribute. This research aimed to identify the characteristics and estimate the value of the visitor's willingness to pay for mangrove conservation efforts on Pahawang Island. This research was conducted in December 2019. The research data was collected using the multistage sampling method. The variables used in this study were willingness to pay, bid, income, education, age, gender, city of origin, marital status and tourism frequency. The results of this study are based on the characteristics of mangrove ecosystem tourists on Pahawang Island, namely, most visitors are willing to contribute to mangrove conservation efforts, come from outside Lampung Province, average age is between 20-29 years, average have a history of high school education, with income is less than Lampung minimum wages (Rp2,432,001.57), most of the respondents are not working and are not married. The result is showing estimated value of the willingness to pay of IDR5,000/individual per visit with an estimated cost of IDR 254,661,000/year.